2006
DOI: 10.1007/s00264-006-0201-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaction allograft with cement for the revision of the femoral component. A minimum 39-month follow-up study with the use of the Exeter stem in Asian hips

Abstract: We report the results of impaction bone grafting of the femoral side in revision total hip arthroplasty in Asian hips (South Korean patients) in which the surgery was performed with the Exeter stem. The minimum follow-up was 39 months (mean, 48.4; range, 39-66). There was subsidence of the cement-graft interface (<1 mm) in three hips (5%), of the stem-cement interface (<1 mm) in 12 hips (21%) and of the stem-cement interface (1-2 mm) in 14 hips (25%). Five hips (9%) developed intraoperative femoral fracture an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…These include the hips with intraoperative fractures and those radiographically defined as definitely loose. These findings agree with the results of Yim et al [45] who found femoral fracture and early subsidence in their series of 56 hips with femoral IBG did not necessarily lead to failure at an average of 39 months' followup. For the majority of stems in Series 2 and 3, cement-bone subsidence was less than 2 mm at 12 months and at up to a maximum of 8 years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These include the hips with intraoperative fractures and those radiographically defined as definitely loose. These findings agree with the results of Yim et al [45] who found femoral fracture and early subsidence in their series of 56 hips with femoral IBG did not necessarily lead to failure at an average of 39 months' followup. For the majority of stems in Series 2 and 3, cement-bone subsidence was less than 2 mm at 12 months and at up to a maximum of 8 years.…”
Section: Discussionsupporting
confidence: 92%
“…Although measures of total stem subsidence are routine, few studies have distinguished stem subsidence at the prosthesis-cement interface from that at the cement-bone interface so as to properly describe the pattern of subsidence after femoral IBG [8,10,14,25,45]. These studies suggest that stem subsidence within the cement mantle occurs in a predictable pattern and support the use of this technique.…”
Section: Introductionmentioning
confidence: 94%
“…The use of impacted bone allograft technique in revision surgery on the femoral side has been reported with good to excellent results over the mid-and long-term [3,7,8,20,23,24]. A prerequisite for its use is containment of the grafts.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was observed that a stable fixation can be difficult to achieve with cement especially in those patients who have poor femoral bone stock1. Some studies showed good clinical results during femoral revision when a cemented stem was used in conjugation with an impacted bone graft234. However, this technique was not widely used clinically because of a high intraoperative and postoperative femoral fracture rate, frequent postoperative subsidence, and prolonged operative time requirements45678.…”
mentioning
confidence: 99%